Treatment of hexavalent chromium using a galvanic flow cell with different flow configurations - Chieng, Hui Yap; Mohamed, Norita (Penerbit Universiti Sains Malaysia, 2004)
Wastewater sources involve two general types, chromium-related and non-chromium wastewaters (Patterson, et al., 1994). Although chromium is present in both the trivalent and hexavalent state in process solutions and wastes, the dominant species is hexavalent chromium (Pollution prevention and control technologies for plating operations, 2000).